Article RETRACTED due to malpractice Practicum programmes and teaching competency development among preservice physical education teachers: a quantitative study from North Africa - bessaoud, thameur (Retos, 2026)
Introduction: Structured practicum programmes are the primary developmental space in physical education teacher education (PETE), yet empirical evidence on the differential development of specific teaching competency domains remains scarce in non-Western contexts, with North Africa conspicuously absent from international reviews. Objective: To examine the extent to which participation in a structured practicum predicts the acquisition of four core teaching competency domains—lesson planning, lesson delivery, classroom management, and assessment—among preservice PE teachers at an Algerian university, and to identify which domains display the largest developmental gaps. Methodology: Cross-sectional survey following STROBE guidelines. Random sample of n = 74 third-year preservice teachers (52 male, 22 female; Mage = 21.8, SD = 1.2) from the ISTAPS, University of Laghouat (N = 177). Instrument: 40-item validated Likert questionnaire (Cronbach’s alpha = .822). Analyses: simple linear regression, one-way ANOVA, within-domain Cohen’s d effect sizes. Results: Practicum participation explained 59.0% of the variance in overall teaching competency (Adj. R2 = .590, 95% CI [.441, .728]; F[1, 72] = 53.47, p < .001; f2 = 1.51). Within-domain Cohen’s d ranged from 0.57 (assessment) to 1.26 (management), revealing a systematic procedural-pedagogical divide between directly supervisable routines and higher-order pedagogical reasoning competencies. Discussion: The procedural-pedagogical divide converges with international evidence from Australia, Chile, Kuwait, Qatar, and Jordan, pointing to a structural limitation of traditional supervision globally rather than a context-specific failure, precisely explained by Kolb’s experiential learning theory. Conclusions: The practicum is a powerful but selectively uneven developer of teaching competencies. Technology-enhanced supervision and explicit assessment literacy training are proposed as evidence-based reforms. Supplementary data are available as online material (Tables S1-S6).